Peran DPS dalam Perlindungan Konsumen terhadap Klausula Eksonerasi di Perbankan Syariah - Amin, Rukhul (Universitas Muhammadiyah Surabaya, 2024)
This research aims to find out the role of the Sharia Supervisory Board (DPS) in efforts to protect islamic banking consumers (customers) against the possibility of exoneration clauses in agreements. This research uses literature study with various references to journals, books and several articles. Library research is research carried out by collecting data and theoretical foundations by reviewing various books, scientific works and previous research related to this research. The research results obtained show that consumer protection against exoneration clauses is classified in two forms, namely preventive and recessive. In the context of preventive protection, the Sharia Penasaw Council, with its various authorities and duties, has a very important role in preventing the use of exoneration clauses in islamic banking